2009
DOI: 10.1111/j.1365-2516.2009.02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy assessment of a new clotting factor concentrate in haemophilia A patients, including prophylactic treatment

Abstract: Currently, efficacy of a new factor concentrate is mostly judged by its ability to achieve haemostasis after a bleeding episode. However, in patients on prophylaxis, the effectiveness in preventing bleeds, and thus joint damage, is most important. An albumin-free recombinant factor VIII (FVIII) concentrate was introduced in the Netherlands in 2004. In this study, the efficacy of a new recombinant plasma/albumin-free FVIII concentrate (rAHF-PFM, Advate) was assessed by comparing bleeding frequency and factor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Twenty‐nine prospective clinical studies reported from 1990 to 2010 with 3012 total patients at risk for de novo inhibitor development were included in the meta‐analysis [10,14–16,32–60]. All were published.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐nine prospective clinical studies reported from 1990 to 2010 with 3012 total patients at risk for de novo inhibitor development were included in the meta‐analysis [10,14–16,32–60]. All were published.…”
Section: Resultsmentioning
confidence: 99%
“…In most countries (including the United States since 2011), rAHF‐PFM is also indicated for prophylaxis to prevent or reduce bleeding. Early studies confirmed the efficacy of rAHF‐PFM . Iorio et al .…”
Section: Introductionmentioning
confidence: 93%
“…It should be noted that this was an open label trial and was not randomized or blinded. A similar design was used in a clinical trial comparing the efficacy of a new FVIII concentrate (Advate) to that of previous treatment documented in the clinic's registry (Den Uijl et al, 2009). Nevertheless, additional data from a larger randomized and blinded clinical trial would be valuable to firmly support the findings of the current study.…”
mentioning
confidence: 99%